BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA DENPASAR DALAM MENANGANI PENGADUAN DAN PENYELESAIAN SENGKETA KONSUMEN - Dwi Weda Astuti, Ida Ayu; Rudy, Dewa Gede; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Consumer Protection Act provides an alternative resolution through outside the judicial system agency called The Consumer Dispute Settlement Agency, beside through a court whose jurisdiction covers the domicile of the consumer. Thus in case of consumer disputes, consumers do not have to litigants through the court, but can pass the existing The Consumer Dispute Settlement Agency at city / county throughout Indonesia.
Keywords: Dispute consumerism, Justice, The Consumer Dispute Settlement Agency